Effectiveness of Kepok Banana (Musa paradisiaca) Bread-Based Adsorbent for Fe(III) Removal Using HCl Activation: Freundlich and Langmuir Isotherm Models - Supraptiah, Endang; Niati, Sri Murda; Hajar, Ibnu; Ningsih, Aisyah Suci; Amalda, Feby Nia; Silviyati, Idha (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2025)
Activated carbon can be synthesized from lignocellulosic biomass, such as kepok banana (Musa paradisiaca) stems, which are an abundant agricultural waste rich in cellulose ( 64%). In this study, kepok banana stems were utilized as a precursor to produce activated carbon using hydrochloric acid (HCl) as the chemical activating agent. The activation process employed HCl concentrations of 1.5, 2.0, 3.0, 5.0, and 7.0 N, with a carbonization temperature of 400 °C for 1 hour and an Fe adsorption contact time of 30 minutes. The resulting activated carbon was evaluated based on its physicochemical properties according to the Indonesian National Standard (SNI 06-3730-1995). The sample treated with 3.0 N HCl showed optimal characteristics, including moisture content of 2.34%, ash content of 0.28%, volatile matter content of 2.05%, and fixed carbon content of 95.33%. Its iodine number reached 1116.98 mg/g, and the Fe ion removal efficiency was 99.14%. FTIR spectroscopy confirmed the presence of functional groups typical of activated carbon—O–H, aromatic C=C, C–H, and C–O—suggesting good adsorption potential. Furthermore, adsorption behavior was analyzed using the Freundlich isotherm model, which describes multilayer adsorption on heterogeneous surfaces. The findings demonstrate that activated carbon derived from kepok banana stems is an effective, low-cost, and environmentally friendly adsorbent for iron removal, suitable for applications in water purification and wastewater treatment.